Detección de anticuerpos para BVDV y BoHV-1 en llamas de la región de Tandil - Provincia de Buenos Aires - Morán, P.E. (2010)
Llama (Lama glama) is the predominant species of South American camelids in Argentine Republic, with an estimated population of 200.000 animals. The increasing of productive activity raised the animals transport and distribution to different regions of the country. As a result, the direct contact of these species with cattle increase opportunities for spreading own and common infectious agents among species. Considering that American camelids are susceptible to pestivirus and herpesvirus infections, it was proposed to carry out a serological searching of neutralizing antibodies to bovine viral diarrhea (BVDV) and bovine herpesvirus 1 (BoHV-1). Forty nine animals from two llama fl ocks in the region of Tandil were analyzed by serum neutralization test on Madin Darby Bovine Kidney cell culture; 22% (11/49) of animals showed antibodies titles against BoHV1, and 2% (1/49) were positive to BVDV. These results suggest that viral circulation occurred into the analyzed population. Continuous searching on these ruminant populations would be necessary in order to identify possible risk factors involved in the epidemiology of these viruses, considering the potential effects on control and eradication programs.\n